Karl Kautsky and the Russian Revolution of 1905: A Debate on the Driving Forces and the Prospects of the Russian Revolution in the Second International. Issue 3 (3rd July 2017) - Avila, Paula; Gaido, Daniel
ABSTRACT: In October 1906 G. V. Plekhanov sent a questionnaire to the leaders of international Social Democracy, requesting their opinion about the class character of the Russian Revolution and the tactics which followed from this analysis for the Russian Social Democratic Labour Party. He received 12 responses, which overwhelmingly supported the Menshevik position: the Russian Revolution was not socialist, at most it was bourgeois revolution with socialist elements; the boycott of the Duma was considered an error and cooperation with the parties of the bourgeois opposition, essential. The exception to this rule was the reply of Karl Kautsky. While Kautsky's answer was cautious enough for both Lenin and Trotsky to consider it as a confirmation of their theories, it categorically rejected the possibility of a coalition with the bourgeoisie, the posture favoured by Plekhanov, and therefore constituted a clear refutation of the Menshevik prospects on the Russian Revolution.